1996
DOI: 10.1002/art.1780390314
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of anti–HTLV‐I antibody in rheumatoid arthritis

Abstract: Objective. To investigate the association between human T lymphotropic virus type I (HTLV‐I) infection and rheumatoid arthritis (RA) in Nagasaki, an area highly endemic for HTLV‐I infection. Methods. Sera from 113 female patients with RA and 19,796 female blood donors were screened for anti–HTLV‐I antibodies with a gelatin particle agglutination kit and confirmed using an immunoblotting kits. Results. The age‐adjusted summary odds ratio of HTLV‐I infection among RA patients, as compared with blood donors, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
8

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 15 publications
3
28
2
8
Order By: Relevance
“…A similar study has been recently performed by Eguchi and colleagues (24) in patients with HTLV-I infection and arthropathy. Those investigators calculated the age-adjustcd summary odds ratio of HTLV-I infection in RA.…”
Section: Epidemiologysupporting
confidence: 57%
“…A similar study has been recently performed by Eguchi and colleagues (24) in patients with HTLV-I infection and arthropathy. Those investigators calculated the age-adjustcd summary odds ratio of HTLV-I infection in RA.…”
Section: Epidemiologysupporting
confidence: 57%
“…These abnormalities closely resemble those in human RA. Moreover, epidemiologic findings have suggested involvement of this virus in some proportion of the population with RA (23). Thus, the HTLV-I Tg mouse model is a unique RA model in which arthritis develops spontaneously via the same pathogen as one found in RA.…”
Section: Conclusion These Observations Suggest That T Cell Activatiomentioning
confidence: 99%
“…Chronic inflammatory diseases, such as myelopathy, uveitis, Sjögren's syndrome, arthritis, bronchoalveolitis, and polymyositis, have been reported to be related to HTLV-I infection (3,4). A study in Nagasaki, Japan showed the HTLV-I positive rate in patients with RA was higher than in blood donors (5). There are studies that have reported HTLV-I-associated arthropathy, which has unique clinical characteristics, such as the involvement of large joints, marked inflammation, and extraarticular symptoms (4,6).…”
Section: Introductionmentioning
confidence: 99%